A guinea pig for conformer selectivity and mechanistic insights into dissociative ionization by photoelectron photoion coincidence: fluorocyclohexane. Issue 4 (14th January 2020) - Wu, Xiangkun; Zhou, Xiaoguo; Hemberger, Patrick; Bodi, Andras
Abstract : PEPICO determines conformer-dependent ionization energies and unveils the fragmentation mechanism of C6 H11 F + . Abstract : We studied fluorocyclohexane (C6 H11 F, FC6) by double imaging photoelectron photoion coincidence spectroscopy in the 9.90–13.90 eV photon energy range. The photoelectron spectrum can identify species isomer and, in this case, even conformer selectively. Ab initio results indicated that the axial conformer has two, close-lying cation electronic states. With the help of Franck–Condon simulations of the vibrational fine structure, we determined the origin of three transitions, (i) axial FC6 → axial FC6 + of C 1 symmetry (X̃ +, A′′ in C S ), (ii) equatorial FC6 → equatorial FC6 + of C 1 symmetry (X̃ +, A′′ in C S ), and (iii) axial FC6 → A′ axial FC6 + of C S symmetry (Ã + ) as 10.12 ± 0.01, 10.15 ± 0.01 and 10.15 ± 0.02 eV, respectively. At slightly higher energies, the FC6 cation starts fragmenting by HF loss ( E 0 = 10.60 eV), followed by sequential CH3 ( E 0 = 10.71 eV) or C2 H4 ( E 0 = 11.06 eV) loss. Surprisingly, the methyl-loss step has an effective barrier of only 0.11 eV, and yet it is a slow process at threshold. Based on the statistical model, this is explained by isomerization and stabilization of the C6 H10 + intermediate. The highest energy channel observed, vinyl fluoride (C2 H3 F) loss yielding C4 H8 + appears in the breakdown diagram at 12 eV, which agrees with the computed threshold to cyclobutane cation formation. However, the model predicted a ca. 1 eV competitive shift for this parallel channel, i.e., an E 0 = 11.23 eV. This led us to explore the potential energy surface to find a lower-lying fragmentation channel including H-transfer steps. Rate constant measurements and statistical modeling thus yield fundamental insights into the reaction mechanism beyond what is immediately seen in the mass spectra.